STUDI MINAT KUNJUNGAN KEMBALI TAMU DI HOTEL KOKOON SURABAYA DENGAN PENGARUH KUALITAS PELAYANAN, CITRA MEREK DAN KEPUASAN TAMU - Andrea Ragil Raharjo; Andhi Supriyadi (LPSDI Bina Patria, 2025)
This study, located at the Kokoon Hotel Surabaya, seeks to evaluate and clarify the impact of service quality, brand image and satisfaction on intention to return visits. One hundred individuals served as the study's sample, after that, they had the chance to respond to a survey which would be processed using the SPSS application and also tested for suitability using validity and reliability tests. Descriptive analysis, multiple regression analysis, model testing, and hypothesis testing are the techniques for analyzing data that are employed. The findings of the research concluded that service quality, brand image and impact on return visit interest. With this, the management of Hotel Kokoon Surabaya is anticipated to be able to get betterof the quality of service, the image of Hotel Kokoon Surabaya as a heritage hotel and increase guest satisfaction so that guests can return to visit to take a nap or just enjoy the atmosphere of the hotel in general.